A-108 Psychological and Sociodemographic Challenges, but Not History of Mild Traumatic Brain Injury, Is Associated with Criminal Justice Involvement among Veterans and Service Members. (30th August 2021) - Gius, Becky; Fournier, Lauren F; Reljic, Tea; Pogoda, Terri; Corrigan, John; Garcia, Amanda; Troyanskaya, Maya; Miles, Shannon
Abstract: Objective: Examine factors associated with history of arrests and felony incarceration among Veterans and Service Members (V/SM) with combat exposure. Method: Participants were V/SM who completed a baseline assessment for the multicenter Chronic Effects of Neurotrauma Consortium study (N = 1555). Most were male (87%), white (72%), with a mean age of 40 years (SD = 9.71). The majority (83%) reported a history of ≥1 mild traumatic brain injury (mTBI), with thirty-five present of those experiencing 3+ mTBIs. Results: Three groups were composed based on self-reported level of involvement with the criminal justice system: 1.) No history of arrests or incarcerations (65%), 2.) A lifetime history of arrest but no felony incarceration (32%), and 3.) A lifetime history of felony incarceration (3%). Chi-square and Kruskal-Wallis H tests revealed statistically significant differences between the groups in demographic factors including the incarcerated group having younger age, greater percentage of men, lower education, and greater percentage of never being married, followed by the arrest group and then the no arrest group (all p < 0.05). The incarcerated group also had the highest level of posttraumatic stress disorder (PTSD) symptoms, lowest social support, and greatest percentage of hazardous alcohol consumption, followed by the arrest and then the no arrest groups (all p < 0.05). No differences were found between groups for mTBI history or neuropsychological testing results. Conclusions: Correlates of legal involvement among V/SM span demographic and psychological dimensions. Some correlates are modifiable, including social support, PTSD symptoms, and alcohol consumption. Addressing these modifiable risk factors is critical to lower the risk of future criminal justice involvement.